Kuwait : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the general situation of money laundering and financing of terrorism is discussed. In addition, the followings are overviewed: financial sector, DNFBP sector, commercial laws and mechanisms governing legal persons, and strategy to prevent money laundering and terrorist financing. A legal framework and criminalization of financing of terrorism are also given. Confiscation, freezing, and seizing are explained under the legal framework. Various preventive measures used are also discussed in this paper. Financial institution secrecy and confidentiality are also outlined.